2018
DOI: 10.1002/ccr3.1946
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic characterization of patients with chronic mucocutaneous candidiasis disease

Abstract: Key Clinical MessageEven if initial immunologic screen is normal, a high index of suspicion for immunodeficiency should guide the evaluation and management of patients with recurrent episodes of mucocutaneous candidiasis. Although rare, a diagnosis of chronic mucocutaneous disease should always be considered in order to improve their outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recently, it has been confirmed that genetic defects of Th17 or its related cytokines can promote the occurrence and development of cutaneous mucosal C. albicans infections such as chronic mucocutaneous candidiasis (CMC) ( 35 ). CMC often appears in patients with profound primary T-cell immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been confirmed that genetic defects of Th17 or its related cytokines can promote the occurrence and development of cutaneous mucosal C. albicans infections such as chronic mucocutaneous candidiasis (CMC) ( 35 ). CMC often appears in patients with profound primary T-cell immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal esophagitis may develop due to achalasia, esophageal cancer, or progressive systemic sclerosis, impairing the esophagus's normal motility. As a result of the creation of small blisters, which burst with time, distinct superficial ulcers may appear on the mucosa in cases of HPV-induced esophagitis [ 28 ]. The host helps the ulcers heal in those with strong immune systems.…”
Section: Reviewmentioning
confidence: 99%